PENGARUH SERTIFIKAT INVESTASI MUDHARABAH ANTARBANK, INFLASI, DAN NILAI TUKAR (RUPIAH) TERHADAP PEMBIAYAAN BANK UMUM SYARIAH DI INDONESIA 2015-2024 - Nursyifa, Ferzie; Kusnadi, Iwan; Ananda, Iva Ashari (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
This study investigates the effects of the Interbank Mudharabah Investment Certificate (Sertifikat Investasi Mudharabah Antarbank/SIMA), inflation, and exchange rates on financing provided by Islamic Commercial Banks in Indonesia during the period 2015–2024. The study employs a descriptive quantitative approach with a focus on causality analysis, utilizing secondary time-series data obtained from Bank Indonesia and the Financial Services Authority (Otoritas Jasa Keuangan/OJK). The data are analyzed using the Vector Autoregression (VAR) estimation method with the assistance of EViews 12 software. Several pre-estimation procedures are conducted, including stationarity testing, optimal lag length determination, and cointegration testing, to ensure the accuracy and validity of the model. The results indicate that although the individual variables become stationary after first differencing, the cointegration test does not reveal any long-run equilibrium relationship among SIMA, inflation, exchange rates, and Islamic bank financing. Granger causality tests demonstrate that Islamic bank financing Granger-causes SIMA, inflation, and exchange rates, but not vice versa. Further VAR analysis reveals dynamic interdependence among the variables, with past values of Islamic bank financing significantly influencing its current level as well as inflation.